2023
DOI: 10.1002/ptr.8002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D‐pinitol on MK‐801‐induced schizophrenia‐like behaviors in mice

Jae Youn Kim,
Chang Hyeon Kong,
Do Yeon Kim
et al.

Abstract: Schizophrenia is a chronic brain disorder characterized by positive symptoms (delusions or hallucinations), negative symptoms (impaired motivation or social withdrawal), and cognitive impairment. In the present study, we explored whether D‐pinitol could ameliorate schizophrenia‐like behaviors induced by MK‐801, an N‐methyl‐D‐aspartate receptor antagonist. Acoustic startle response test was conducted to evaluate the effects of D‐pinitol on sensorimotor gating function. Social interaction and novel object recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…D-Pinitol, a trimethyl analogue of DCI, is widely present in the owers and leaves of Pinus species, legumes, and many other plants and acts like insulin [41]. D-Pinitol has been reported to treat schizophrenia in mice by down-regulating the transcription factor NF-κB and proin ammatory cytokines in the prefrontal cortex [42]. Our previous studies have shown that DCI can enhance the antioxidant capacity and health lifespan of C. elegans, and delay the development of neurodegenerative diseases in C. elegans [16].…”
Section: Discussionmentioning
confidence: 99%
“…D-Pinitol, a trimethyl analogue of DCI, is widely present in the owers and leaves of Pinus species, legumes, and many other plants and acts like insulin [41]. D-Pinitol has been reported to treat schizophrenia in mice by down-regulating the transcription factor NF-κB and proin ammatory cytokines in the prefrontal cortex [42]. Our previous studies have shown that DCI can enhance the antioxidant capacity and health lifespan of C. elegans, and delay the development of neurodegenerative diseases in C. elegans [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is also a responsibility and challenge that medical professionals must face. Schizophrenia is a serious mental illness characterized mainly by positive symptoms, negative symptoms, and cognitive deficits [ 5 , 6 ]. While anti-schizophrenia medications currently on the market can relieve positive and negative symptoms, they cannot effectively combat cognitive impairment, often leading to more serious side effects.…”
Section: Introductionmentioning
confidence: 99%